2001
DOI: 10.1017/s1355838201001704
|View full text |Cite
|
Sign up to set email alerts
|

Functional mapping of ribosome-contact sites in the ribosome recycling factor: A structural view from a tRNA mimic

Abstract: Ribosome recycling factor (RRF) is required for disassembly of the posttermination complex of the ribosome after release of polypeptides. The crystal structure of RRF resembles a tRNA shape, with an architecturally different flexibility compared with tRNA, but its structure-and-function relationships are unknown. We here found that an RRF variant defective in ribosome binding regains the binding capacity through 20 independent secondary changes occurring in three topologically distinct regions of RRF. Because … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 19 publications
2
25
0
Order By: Relevance
“…However, the gaps in our understanding of the mechanistic aspects of RRF function present a major limitation in the exploitation of this factor as a novel drug target. Mutational analyses, a crucial facet of structure-function studies, are important for a better understanding of the mechanism of action of RRF Fujiwara et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the gaps in our understanding of the mechanistic aspects of RRF function present a major limitation in the exploitation of this factor as a novel drug target. Mutational analyses, a crucial facet of structure-function studies, are important for a better understanding of the mechanism of action of RRF Fujiwara et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The creation of similar mutations in E. coli RRF (EcoRRF) showed that mutants which lacked up to seven residues from the Cterminal end were still functional. However, deletions that resulted in the loss of nine or more residues from the C-terminal end were defective in ribosome recycling (Fujiwara et al, 2001 ;Janosi et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…We suggest that this site is the same site where ec-RRF is moved to and released from the ribosomes during normal disassembly of the post-termination complexes. This hypothesis is supported by the fact that tt-RRF functions in E. coli that have defective ec-RRF (Fujiwara et al 2001). Therefore, binding of tt-RRF to ec-ribosomes described here is identical to that of ec-RRF.…”
Section: Wwwrnajournalorgmentioning
confidence: 94%
“…RRF is an essential protein in prokaryotes (Janosi et al 1994) and eukaryotes also (Rolland et al 1999;Teyssier et al 2003). The biological importance of RRF was further supported by isolation of a number of RRF mutants (Janosi et al 1998Fujiwara et al 1999Fujiwara et al , 2001) that have lethal effects. In the absence of RRF, ribosomes are not released from mRNA and start unscheduled translation downstream of the termination codon (Janosi et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…RRFs whose structures have been determined to be a strict L-shape, were obtained from thermophilic bacteria and did not show polysome breakdown activity in vitro system containing EF-G and puromycin-treated polysome fraction from E. coli (11)(12)(13). RRFs that demonstrated activity in that system were only mesophilic bacteria, i.e.…”
mentioning
confidence: 99%